Rape of a Minor: Criminal Sanctions and Law Enforcement Efforts - Putra Zai, Aca Surya (Jurnal Hukum dan Keadilan, 2024)
Rape that occurs in minors is a form of sexual violence that is increasingly concerning in Indonesia, which has serious impacts on the physical, mental, social development of victims and adverse effects on the child's developmental psychology. Children who experience the crime of sexual intercourse can experience deep trauma because in essence children must receive love and protection. The purpose of this study is to determine the criminal sanctions imposed on the perpetrators and to determine the law enforcement efforts made in dealing with this case. This study uses normative juridical research because this study discusses applicable legal regulations, such as the Child Protection Law and the Sexual Violence Crime Law (TPKS), which regulate the types and severity of punishment for perpetrators of rape. The results of this study indicate that criminal sanctions against perpetrators of child rape can include imprisonment, fines and additional penalties. However, law enforcement efforts face various obstacles, such as limited evidence, social stigma and internal factors of rape victims, in addition, legal protection efforts for children who are victims of rape are still lacking and not commensurate with the losses suffered by rape victims.